2016
DOI: 10.1039/c6ra02685k
|View full text |Cite
|
Sign up to set email alerts
|

A newly designed softoxometalate [BMIm]2[DMIm][α-PW12O40]@hydrocalumite that controls the chain length of polyacrylic acid in the presence of light

Abstract: We have controlled the radical as well as cationic polymerization of acrylic acid using [BMIm]2[DMIm][α-PW12O40]@hydrocalumite (SOM 2) as a photocatalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…We demonstrated earlier that such a micro-bubble formed on a glass substrate drives self assembly of mesoscopic material in an aqueous dispersion due to hydrodynamic (Marangoni) flows caused by the temperature (and the resultant surface tension) gradient across the bubble. 21 At the core of the process is a soft oxometalate (SOM) material [22][23][24][25][26] which absorbs at the laser wavelength of 1064 nm to form a micro-bubble. SOMs self-assembled at the bubble base subsequently undergo a phase transition from the soft to crystalline state 21 as the bubble is translated by the optical tweezers.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated earlier that such a micro-bubble formed on a glass substrate drives self assembly of mesoscopic material in an aqueous dispersion due to hydrodynamic (Marangoni) flows caused by the temperature (and the resultant surface tension) gradient across the bubble. 21 At the core of the process is a soft oxometalate (SOM) material [22][23][24][25][26] which absorbs at the laser wavelength of 1064 nm to form a micro-bubble. SOMs self-assembled at the bubble base subsequently undergo a phase transition from the soft to crystalline state 21 as the bubble is translated by the optical tweezers.…”
Section: Introductionmentioning
confidence: 99%
“…We have already shown that this cluster is photoactive and it acts as a catalyst in photochemical dimerization followed by oxidation reaction of styrene [42]. Now here we have shown that acrylic acid gets decarboxylated in the reaction medium and further couples with iodobenzene to form styrene in reaction mixture using [Mo 132 ] as a photocatalyst.…”
Section: Resultsmentioning
confidence: 89%
“…Also polyoxometalates are photoactive and generally stable under photochemical conditions. POMs have been used as photocatalyst in different photopolymerization reaction and organic reactions by us already [38][39][40][41][42]. Thus we are now interested to use those giant POMs in photo catalytic organic coupling reaction.…”
Section: Introductionmentioning
confidence: 99%
“…We have used SOM 1 as a photocatalyst for photochemical water oxidation coupled with organic reactions. We have previously shown the photocatalytic activity of the phosphotungstate based inorganic material . The photocatalytic experiments are performed without any external photosensitizer.…”
Section: Resultsmentioning
confidence: 99%